Coronary heart disease mortality in treated familial hypercholesterolaemia: Update of the UK Simon Broome FH register. (July 2018) - Humphries, S.E.; Cooper, J.A.; Seed, M.; Capps, N.; Durrington, P.N.; Jones, B.; McDowell, I.F.W.; Soran, H.; Neil, H.A.W.; ,
Abstract: Background and aims: Patients with familial hypercholesterolaemia (FH) have an elevated risk of coronary heart disease (CHD). Here we compare changes in CHD mortality in patients with heterozygous (FH) pre 1992, before lipid-lowering therapy with statins was used routinely, and in the periods 1992–2008 and 2008–2016. Methods: 1903 Definite (DFH) and 1650 Possible (PFH) patients (51% women) aged 20–79 years, recruited from 21 lipid clinics in the United Kingdom and followed prospectively between 1980 and 2016 for 67, 060 person-years. The CHD standardised mortality ratio (SMR) compared to the population in England and Wales was calculated (with 95% Confidence intervals). Results: There were 585 deaths, including 252 from CHD. Overall, the observed 2.4-fold excess coronary mortality for treated DFH post-1991 was significantly higher than the 1.78 excess for PFH (35% 95% CI 3%–76%). In patients with DFH and established coronary disease, there was a significant excess coronary mortality in all time periods, but in men it was reduced from a 4.83-fold excess (2.32–8.89) pre-1992 to 4.66 (3.46–6.14) in 1992–2008 and 2.51 (1.01–5.17) post-2008, while in women the corresponding values were 7.23 (2.65–15.73), 4.42 (2.70–6.82) and 6.34 (2.06–14.81). Primary prevention in men with DFH resulted in a progressive reduction in coronary mortality over the three time-periods, with no excess mortality evident post-2008 (0.89 (0.29–2.08)), although in women the excess persisted (post-2008 3.65 (1.75–6.72)). Conclusions: The results confirm the benefit of statin treatment in reducing CHD mortality, but suggest that FH patients with pre-existing CHD and women with FH may not be treated adequately. Highlights: 1903 Definite (DFH) and 1650 Possible (PFH) patients followed between 1980 and 2016. Post 1992 treated DFH patients had 35% higher coronary mortality than PFH patients. In DFH men without CHD, coronary mortality was not significantly elevated post 2008. In DFH women coronary mortality was significantly elevated at all times. Suggests that, compared with men, women with FH may not be being treated adequately.